Nurturing Character: A Comparative Study Of Elementary Education In Indonesia And Japan - Aulia, Egi Dina; Saputro, Bayu Aji (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2024)
Character education is crucial for addressing the negative impacts of technology on children's development. In this context, schools play a vital role in shaping individuals according to the norms and rules prevalent in society. This research aims to describe the efforts made in character development among elementary school students in Indonesia and to compare these efforts with those implemented in the Japanese education system. Through a literature study, this research explores the concrete steps taken by schools to improve character education.The findings indicate that support from the community, non-governmental organizations, and the government in Japan holds significant potential for adoption by schools in Indonesia. Several effective practices identified, such as integrated approaches and community support, can enhance the quality of character education in elementary schools. By implementing these methods, it is expected that schools in Indonesia can produce students who are not only academically intelligent but also possess good moral values and social responsibility. The role of school leaders is crucial in ensuring effective character education by managing the available support and resources to achieve these goals.